Chemical Analysis of Sea urchin Diademasetosum Gonads - Mohamad Haikal K. Djafar; Margaretha Solang; Marini Susanti Hamidun; Aryati Abdul; Syam S. Kumaji; La Nane (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Sea urchins Diademasetosum can be found in shallow waters. Sea urchin gonads are nutritionally valuable and capable of accumulating heavy metals. This study aims to determine the moisture content, ash, protein, fat, carbohydrate, Pb, Cd metal content and determine the Maximum Tolerable Intake (MTI) of sea urchin D. setosum gonads. Gonad samples were obtained from three coasts of Huangobotu, Botubarani and Kurenai, Kabila Bone Sub-district, Bone Bolango Regency, using a purposive sampling technique. Gonads were analyzed proximate, including moisture, ash, protein, fat and carbohydrate content. Analysis of Pb and Cd levels using an atomic absorption spectrophotometer. The results were analyzed statistically using One-Way ANOVA Test. The results showed that the average moisture, ash, protein, fat, and carbohydrate content of gonads on the coast of Huangobotu, Botubarani, and Kurenai were significantly different (p0.005); moisture content 71.91%, 75.04%, 78.51%; ash content 1.88%, 1.15%, 2.76%; protein content 9.90%, 12.81%, 15.53%; fat content 7.33%, 3.05%, 4.84%; carbohydrate content 2.35%, 7.92%, 4.93%. Pb levels were significantly different (p0.005) 0.063 mg/kg, 0.039 mg/kg, and 0.018 mg/kg, respectively; Cd levels were not significantly different (p0.005) 0.020 mg/kg, 0.012 mg/kg, 0.014 mg/kg respectively. MTI Pb adults 23.8kg, 38.4kg, 83.3kg, children 5.9kg, 9.6kg, 20.8kg. MTI Cd adults 21kg, 35kg, 30kg, children 5.25kg, 8.75kg, 7.5kg. D. setosumhas potential as a source of protein and can be utilized as food by considering the MTI value.